PAEDIATRIC WEIGHT CUFFS - Rizwan, Mohd; Aziz, Saba (International Journal of Psychosocial Rehabilitation, 2025)
Pediatric weight cuffs are specialized devices designed to enhance strength training and rehabilitation for children, helping improve muscle development, bone health, and overall physical performance. These cuffs, worn around the wrist, ankle, or forearm, provide a controlled resistance during exercises, promoting safe muscle and bone conditioning without overstressing developing joints or soft tissues. Weight cuffs are increasingly used in pediatric rehabilitation to prevent conditions like osteoporosis and osteoarthritis, and they play a crucial role in injury prevention. This paper explores the application of pediatric weight cuffs in resistance training, their benefits for children with special health conditions, and the guidelines for safe use in young populations. Key considerations include age-appropriate resistance levels, proper supervision, and technique to ensure safe, effective training. Special focus is given to the importance of starting resistance training in children over the age of 6-7 years, emphasizing low-intensity exercises and gradual progression. The role of weight cuffs in pediatric health and fitness programs, as well as their benefits in enhancing physical fitness and reducing injury risk, is beneficial.